2022
DOI: 10.1021/acsabm.2c00393
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Biosensor Based on l-Arginine and rGO-AuNSs Deposited on the Electrode Combined with DNA Probes for Ultrasensitive Detection of the Gastric Cancer-Related PIK3CA Gene of ctDNA

Abstract: Gene biomarkers of circulating tumor DNA (ctDNA) in liquid biopsies have been explored for use in the precise diagnosis of tumors. There is a great clinical need to realize the ultrasensitive detection of gene biomarkers in ctDNA. Here we reported that an ultrasensitive label-free biosensor was developed for the detection of the gastric cancer-related PIK3CA gene of ctDNA in peripheral blood. The polymeric L-arginine and graphene oxide-wrapped gold nanostars (rGO-AuNSs) were prepared and deposited on the glass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…A high-sensitivity, low-cost, and noninvasive biosensor to directly detect miRNA21 (a potential biomarker for predicting chronic lung disease in premature infants) in the plasma of breast cancer patients based on p-DNA-rGO-FET with 1fM of LOD was developed by Cai et al, 224 as shown in Figure 13a. On the other hand, Rahman et al 225 reported an ultrasensitive label-free biosensor for detecting gastric-cancer-related PIK3CA gene of ctDNA in peripheral blood, as shown in Figure 13b. DNA probes were immobilized on electrodes comprising polymeric L-arginine and rGO decorated with gold nanostars (rGO-AuNSs).…”
Section: Carbon Dots (Cds)mentioning
confidence: 99%
See 1 more Smart Citation
“…A high-sensitivity, low-cost, and noninvasive biosensor to directly detect miRNA21 (a potential biomarker for predicting chronic lung disease in premature infants) in the plasma of breast cancer patients based on p-DNA-rGO-FET with 1fM of LOD was developed by Cai et al, 224 as shown in Figure 13a. On the other hand, Rahman et al 225 reported an ultrasensitive label-free biosensor for detecting gastric-cancer-related PIK3CA gene of ctDNA in peripheral blood, as shown in Figure 13b. DNA probes were immobilized on electrodes comprising polymeric L-arginine and rGO decorated with gold nanostars (rGO-AuNSs).…”
Section: Carbon Dots (Cds)mentioning
confidence: 99%
“…(b) Gastric cancer sensor based on l -arginine and rGO-AuNSs. Reprinted with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Carbon-based Nanomaterials (Cbns)mentioning
confidence: 99%
“…They accomplished improvements in selectivity and specificity, facilitating superior ctDNA analysis, with the detectable ctDNA concentration ranging from 1.0 � 10 −20 to 1.0 � 10 −10 M (Figure 5A). To enable accurate early cancer screening, Rahman et al 92 designed an extremely sensitive label-free biosensor for the detection of the PIK3CA gene associated with gastric cancer in ctDNA The use of DNA nanotechnology in signal amplification is mainly to achieve increased sensitivity for target detection. [115][116][117][118] Chai et al reported a groundbreaking approach involving a platform based on DNA TP and three-way junction nanostructures, aimed at detecting ctDNA.…”
Section: Ctdnamentioning
confidence: 99%
“…12,13 This process suffers from the drawbacks of a long operational time and needs a special immobilization site on the electrode surface. In addition, to ensure a tight immobilization of DNA probes, the extra functional groups such as amino, 14,15 thiol, 16,17 or biotin 18,19 are necessary to be modified on the probe DNA to realize the covalent reaction, self-assembly, or bioaffinity, which inevitably increases the fabrication cost of the biosensors. In recent years, homogeneous hybridization-based electrochemical DNA biosensors have attracted considerable attention due to their immobilization-free, high hybridization rate/effectiveness, and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the conventional electrochemical nucleic acid (NA) biosensors are constructed in heterogeneous hybridization, which requires immobilization of the probe DNA (pDNA) on the electrode surface. , This process suffers from the drawbacks of a long operational time and needs a special immobilization site on the electrode surface. In addition, to ensure a tight immobilization of DNA probes, the extra functional groups such as amino, , thiol, , or biotin , are necessary to be modified on the probe DNA to realize the covalent reaction, self-assembly, or bioaffinity, which inevitably increases the fabrication cost of the biosensors. In recent years, homogeneous hybridization-based electrochemical DNA biosensors have attracted considerable attention due to their immobilization-free, high hybridization rate/effectiveness, and low cost. Nevertheless, this type of biosensor is commonly dependent on the nuclease-assisted cleavage to achieve the release of labeled electroactive tags such as ferrocene or methylene blue and cyclic signal amplification, which will increase the cost, procedure, and instability of the analysis.…”
Section: Introductionmentioning
confidence: 99%